Perancangan Functional Minimalism Compact Booth Untuk Display Pakaian dan Footwear - Aileen Agustine Palim; Lintu Tulistyantoro; Hendy Mulyono (Intra, 2017)
High market interest of the creative industry can be seen from the frequent exhibitions or events held, one of is in Surabaya. The fashion sub-sector (clothing - footwear products) has a fairly dominant market interest in this creative industry. A brief and non-binding exhibition is a media channel that is often chosen by business owners to offer their products and services.Time limitations result in tenants paying little attention to the way the product arrangements they offer. Design a booth with a good arrangement without realizing it can attract the attention of visitors by itself.FuNC Booth is one of the innovative display systems in the interior of showrooms intended to facilitate business owners in setting up and dismantling the booth they use. The incorporation of compact, modular, knockdown and tensioned systems provides convenience in various aspects including unloading and mobilization. This design method adapted from John Nash has the following stages; Discovery, interpretation, ideation, experimentation and evolution.